2018
DOI: 10.4300/jgme-d-17-00467.1
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Immediate Performance in Neonatal Resuscitation Through Rapid Cycle Deliberate Practice Training

Abstract: Immediately following RCDP interns had improved observed abilities and decreased time to perform critical interventions in NR simulation as compared to those trained with the simulation debriefing. RCDP was not superior in improving confidence level or retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 13 publications
6
65
0
Order By: Relevance
“…The ScopRev [ 1 0 0 7 _ T D $ D I F F ] 14b identified 1 RCT 15 and 3 observational studies of preintervention and postintervention design. 16À 18 One study considered video debriefing, 16 1 considered the use of a checklist combined with video debriefing, 18 and 1 considered the use of a checklist with a team prebrief/debrief as the key element in a quality improvement bundle.…”
Section: Summary Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…The ScopRev [ 1 0 0 7 _ T D $ D I F F ] 14b identified 1 RCT 15 and 3 observational studies of preintervention and postintervention design. 16À 18 One study considered video debriefing, 16 1 considered the use of a checklist combined with video debriefing, 18 and 1 considered the use of a checklist with a team prebrief/debrief as the key element in a quality improvement bundle.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…17 The RCT determined whether there was benefit to rapid cycle deliberate practice compared with standard simulation debriefing. 15 This entire ScopRev [ 1 0 0 8 _ T D $ D I F F ] 14b can be found in Supplement Appendix B-1.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…It allows for feedback to be provided and areas for improvement to be identified as mistakes are made, rather than reflectively at the end of the scenario, and allows the level of difficulty to adjust to the competency of the learner. Studies have shown significant improvement in learner skills using RCDP [16, 18, 19]. Traditional simulation debriefing typically occurs at the end of the resuscitation with a longer period of time to reflect on performance and develop plans for modifications to use during subsequent resuscitations [20].…”
Section: Introductionmentioning
confidence: 99%
“…Rapid Cycle Deliberate Practice (RCDP) as a method of within-event debriefing has been shown to improve pediatric resident resuscitation [5]. It has also been shown to be an effective teaching method for neonatal resuscitation training [6]. When using RCDP, we allow learners multiple opportunities to “do it right” while giving them direct feedback until they master the skill [5].…”
Section: Introductionmentioning
confidence: 99%